Cost Analysis of Outpatient Anterior Cruciate Ligament Reconstruction: Autograft versus Allograft - Nagda, Sameer H. (Springer-Verlag, 2009)
BACKGROUND: Prior studies suggest the cost of allograft anterior cruciate ligament (ACL) reconstruction is less than that for autograft reconstruction. Charges in these studies were influenced by patients requiring inpatient hospitalization. QUESTION/PURPOSE: We therefore determined if allograft ACL reconstruction would still be less costly if all procedures were performed in a completely outpatient setting. METHODS: We retrospectively reviewed 155 patients who underwent ACL reconstruction in an ambulatory surgery center between 2001 and 2004; 105 had an autograft and 50 had an allograft. Charges were extracted from itemized billing records, standardized to eliminate cost increases, and categorized for comparison. Surgeon and anesthesiologist fees were not included in the analysis. Groups were compared for age, gender, mean total cost, mean cost of implants, and several other cost categories. RESULTS: The mean total cost was $5465 for allograft ACL reconstruction and $4872 for autograft ACL reconstruction. There were no differences in complications between the two groups. CONCLUSIONS: Allograft ACL reconstruction was more costly than autograft ACL reconstruction in the outpatient setting. The cost of the allograft outweighs the increased surgical time needed for harvesting an autograft. LEVEL OF EVIDENCE: Level II, economic and decision analyses. See Guidelines for Authors for a complete description of levels of evidence.